Ooxtaxonomy of eight Tettigonoidea species (Insecta: Orthoptera), description and comparison of the egg morphology. (September 2017) - Franch Sas, Marta; Olmo-Vidal, Josep M.; Roca-Cusachs, Marcos; Pujade-Villar, Juli
Highlights: Make a morphological description of the eggs of the studies species and find the micropillar area. Use ootaxonomy as a tool to distinguish and group taxa. Abstract: In the present study, eggs of eight species of the Tettigonoidea superfamily have been examined with the aim to find characteristic traits of each of the studied taxa. In addition, we aim to distinguish them through their eggshell morphology, a technique that nowadays is known as ootaxonomy. All the eggs analysed belong to four subfamilies of the Tettigoniidae family (Bradyporinae: Ephippiger diurnus cunii, Parasteropleurus perezii, Lluciapomaresius panteli, L. ortegai, Tettigoniinae: Decticus verrucivorus, Antaxius hispanicus, and Meconematinae: Cyrtaspis scutata ) and from family Phaneropteridae: Phaneroptera nana . Observations and comparisons were made after optical and Scanning Electron Microscope (SEM) photographs. In all katydids evaluated, we observed that hexagonal cells usually compose the chorion, nevertheless, in some cases egg surfaces appearance is follicular or smooth. Micropylar areas are different among the species examined. Ootaxonomy allowed us to differentiate between the genera studied and the two more related species: Lluciapomaresius panteli and L. ortegai .